Department of Pharmaceutics: innovating ideas into invention / Ahmad Assakir Ahmad Shukri - Ahmad Shukri, Ahmad Assakir (Faculty of Pharmacy, 2024)
Pharmaceutics is a branch of pharmacy that focuses on the formulation, development, and optimization of active pharmaceutical ingredients (API) to ensure their safe effective use by consumers. For instance, while consuming sweet wormwood plants directly to obtain their antimalarial properties may result in an unpleasant experience, opting for artemisinin in pill form is a more feasible and tolerable alternative. Extracting the artemisinin from Artemisia and turning it into edible dosage form is an example of how advancements in pharmaceutics have facilitated improvements in our quality of life. Moreover, this advancement ensured that consumers are required to ingest only a minimal quantity of these pills, thanks to ongoing research in this field. If you have a promising idea for a pharmaceutical product, you will need the proper equipment to develop it. At the Department of Pharmaceutics, we provide the necessary tools and support to help you transform your concept into reality.